Understanding the Experiences of Mauritian Students at Institutions of Higher Education Overseas (Journal of Student Affairs in Africa, 2022)
Each year, a significant number of students from the Indian Ocean island of Mauritius seek higher education opportunities abroad. Yet, limited research exists on these students’ expectations, preferences, and experiences in their academic and non-academic university settings overseas. This quantitative study investigates the experiences of Mauritian degree-seeking students at universities in Australia and the United Kingdom, which have been two of their most preferred destination countries for Mauritian international students over the years. It specifically examines associations between overall university satisfaction and various aspects of the student experience in the arrival, learning, living, and support services environment. Analyses from this research reveal that a number of satisfaction variables were important to students, namely the opportunity to make friends on campus, the availability of social activities and facilities, internet access and IT support, and chaplaincy or multi-faith provision. Implications for international educators, university administrators, and guidance counselors are discussed.